Dural Thickening of the Internal Auditory Canal in Patients With Spontaneous Intracranial Hypotension Syndrome. Issue 2 (March 2016) - Hori, Saeka; Taoka, Toshiaki; Miyasaka, Toshiteru; Ochi, Tomoko; Sakamoto, Masahiko; Wada, Takeshi; Myochin, Kaoru; Takayama, Katsutoshi; Kichikawa, Kimihiko
Abstract : Objective: This study aimed to assess the utility of dural thickening of the internal auditory canal (IAC) in patients with spontaneous intracranial hypotension (SIH) syndrome and determined the sensitivity and specificity of this image finding. Methods: Magnetic resonance images were evaluated for 22 cases of definite SIH and 16 cases of unlikely SIH. On contrast-enhanced magnetic resonance imaging, pachymeningeal enhancement and dural thickening of the IAC were assessed. Results: Pachymeningeal enhancement was observed in 21 of 22 patients in the definite SIH group and 1 of 16 patients in the unlikely SIH group (sensitivity, 95.5%; specificity, 93.8%). Dural thickening of the IAC was observed in 15 of 22 patients in the definite SIH group and 0 of 16 patients in the unlikely SIH group (sensitivity, 68.2%; specificity, 100%). Conclusions: Dural thickening of the IAC showed 100% specificity for SIH syndrome and can increase the accuracy of diagnosis of SIH syndrome.